Curriculum Disruption: A Vision for New Practices in Teaching and Learning - Bradley Conrad; Christy M. Moroye; P. Bruce Uhrmacher (Arizona State University, 2015)
With increased attention to measurable, common student achievement outcomes, the experience of both students and teachers has been overlooked. While measurable outcomes may possess value, they have served to shift the focus of schools, administrators, and teachers to writing curriculum that centers on assessable content learning rather than meaningful educational experiences for teachers and students alike. This study of a recent teacher workshop examines a lesson planning approach that is based on John Deweys notion of the aesthetic experience and places such experiences at the heart of the educational enterprise. Findings include the notion of curriculum disruption, which refers to an alteration of the improvement trajectory of standardized curricula, offering innovation in lesson planning.